Evaluation of laboratory Short-term ageing and rutting Characterisation of bitumen and Asphalt mastics /Noor Halizah Binti Abdullah - Awam, Pusat Pengajian Kejuruteraan (2018)
In Malaysia, the most prevalent form of surface distress is top down cracking due to repeated loading accelerated by bitumen ageing. Ageing also causes structural and functional failures in asphalt pavement. According to international laboratory standards (ASTM D2872), short-term ageing is simulated by conditioning the bitumen in the rolling thin-film oven (RTFO) test. However, several researchers reported some discrepancies between the results obtained from the RTFO and field ageing. This thesis presents a short-term ageing procedure that was developed using response surface method, to determine the corresponding ageing duration and temperature that best mimicked ageing that took place during asphalt production in the Malaysian asphalt mixing plant. The optimization procedure suggested ageing protocols equivalent to conditioning at 170°C over a 132 minutes duration which corresponded to the measured bitumen properties recovered from site. Ageing duration and temperature were significant factors affecting the physical and rheological properties of short-term aged bitumen. Rheological characterisation indicated that bitumen viscosity increased with ageing severity and improved rutting resistance of bitumen. The stiffening effects were found to be dependent on bitumen type, ageing temperature and duration, and test temperature. The rheological master curves of bitumen and asphalt mastics were described using the two springs, two parabolic creep elements and one dashpot (2S2P1D) Model. This model was found to accurately describe the rheological properties of both unaged and aged bitumen and asphalt mastics. The cumulative shear strain showed slightly higher magnitudes of recoveries for 60/70 penetration grade bitumen obtained from Quarry B compared to 80/100 penetration grade bitumen from Quarry A and B. Meanwhile, asphalt mastics prepared using 60/70 base bitumen incorporating 60% hydrated lime always showed higher recoveries. Short-term ageing generally reduced non-recoverable compliance (Jnr) and increased percentage recovery (R) of the bitumen and asphalt mastics. Based on the comparison between rutting indicators, good correlations were found between Superpave rutting parameter (G*/sin δ) and Jnr for both bitumen and asphalt mastics. Hydrated lime filler always registered greater rutting resistance compared to asphalt mastics prepared using ordinary Portland cement. The activation energy (AE) of asphalt mastics tested between 45 to 65°C indicated a reduction in AE with higher frequency, while higher filler content and ageing increased AE. These findings were also similar for samples tested at temperatures ranging from 5 to 35°C. AE was found to be influenced by bitumen type, filler type, filler content, frequency and temperature range. It was concluded that the standard RTFO procedure was unable to simulate the actual short-term ageing that occurs on site. Ageing improved rutting resistance and hydrated lime showed higher stiffening effects compared to ordinary Portland cement.